Psychological Resources Protect Well-Being During the COVID-19 Pandemic: A Longitudinal Study During the French Lockdown - Pellerin, Nicolas; Raufaste, Eric (Frontiers in Psychology, 2020)
This longitudinal study investigated the capability of various positive psychological resources to directly or indirectly protect specific well-being outcomes and moderate the effects on well-being of health and economic threats in a lockdown situation during the 2020 health crisis in France. At the beginning of lockdown (wave 1), participants (N=470) completed self-assessment questionnaires to document their initial level of well-being and of nine well-established psychological resources, measured as traits: optimism, hope, self-efficacy, gratitude toward the world, self-transcendence, wisdom, gratitude of being, peaceful disengagement, and acceptance. Three weeks later, a weekly follow-up was started to record changes in well-being and reported threats during five weeks (waves 2-6). Results show that psychological resources efficiently protected well-being in a variety of ways: They buffered the adverse effects of reported threats to health and wealth, increased the well-being averages, and reduced the decline in well-being over time. More specifically, emotional well-being was positively predicted by hope, gratitude of being and, to a lesser level, by acceptance; psychological well-being by self-efficacy, personal wisdom, and gratitude of being; social well-being only by gratitude toward the world; and inner well-being by optimism, gratitude of being, and acceptance. The study emphasizes the importance of cultivating psychological resources in ordinary times to protect individuals' well-being when difficult and extraordinary circumstances occur. It also offers clues to the kind of resources one may want to develop.